Isolated tubal torsion in a woman who had laparoscopic tubal ligation by bipolar electrocoagulation - (:unkn) unknown (My University, 2013)
Rebound, defansı olmayan sol alt kadran ağrısı olan 29 yaşındaki kadın hastaneye yatırıldı. Pelvik muayenesinde sol forniks komşuluğunda ağrılı, yarı mobil, yarı sert 6 cm çapında kitle palpe edildi. Medikal öyküsünde 2 ay önce bipolar koter ile laparoskopik tuba ligasyonu haricinde bir özellik yoktu. 48 saat medikal tedavi sonrası laparoskopi yapıldı. Rahim ve yumurtalıklar normal görünümdeydi. Sol tüpün distal bölümü mezosalpinks etrafında 3 kez dolanmıştı ve gangrenli, nekrotik görülüyordu. Sol parsiyel salpinjektomi yapıldı. Ameliyattan 8 saat sonra kadın taburcu edildiPatoloji dilate tüpün torsiyonunu teyid etti.

ABSTRACT A 29-year-old woman with tenderness in the left lower quadrant othe abdomen with no guarding or rebound tenderness was admitted to the hospital. Her pelvic examination revealed a tender, semi-mobiland semi-solid mass, 6 cm in diameter, just palpable adjacent to thleft fornix. Her medical history was otherwise normal except thashe had had laparoscopic tubal ligation by bipolar cauterization two months earlier. After 48 hours of medical treatment, laparoscopy was performed. The uterus and both ovaries appeared normalThe distal portion of the left tube remnant was twisted three timeon its mesosalpinx and appeared gangrenous and necrotic. A lefpartial salpingectomy was done laparoscopically. The woman wadischarged after 8 hours from the hospital. The pathology confirmed the diagnosis of torsion of a previously dilated tube.
Bipolar elektrokoteri ile bilateral tuba ligasyonu olan kadında izole tubal torsiyon
Keywords: Genel ve Dahili Tıp